Climatic Responses of Himalayan Silver fir (Abies spectabilis) from Tree Line of Dolpa, Northewestern Nepal - Ghimire, Shiba Raj; Gaire, Narayan Prasad; Shrestha, Uttam Babu; Shrestha, Bharat Babu (Journal of Physical and Life Sciences, 2024)
Identifying the relationship between climate and tree-ring growth is a basis for the climatic reconstruction using tree-ring as proxy of past climate. Himalayan Silver Fir (Abies spectabilis), an endemic species of the Himalaya, is one of the potential species for dendroclimatological studies. In this communication, we report the growth responses of A. spectabilis from marginal area to climatic parameters using tree-ring chronology. A total of 102 tree core samples from 90 trees were collected from nine quadrats of 20 m x 20 m size located along elevation gradient between 3590 m and 3730 m a.s.l. in Dolpa district of Nepal. A 235–year long tree–ring width chronology of A. spectabilis, dating back to 1777, was developed. A quantitative analysis between tree growth and climate, based on a correlation and response function showed that the radial growth of the species was mainly limited due to temperature induced moisture stress during spring season having negative relationship with mean maximum temperature of March (r2 = 0.43, p < 0.05) and May (r2 = 0.55, p < 0.01), and mean temperature of May (r2 = 0.43, p < 0.05) of the current year and positive relation with the precipitation of the same season. If the current scenario of rapid increasing trend in temperature and decreasing trend in precipitation will continue in the region, it will have an adverse implication in the growth of the species with future climate change.